Agronomic biofortification of grain crops with zinc in association with plant growth-promoting bacteria - Jalal, Arshad [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
The intensive cropping system to pursue high grain production and feed the fast-growing global population has disturbed agricultural sustainability and nutritious security due to the imbalance use of chemical fertilizers. There is an urgent need to understand soil micronutrients deficiency and their impact on crop nutrition and productivity. Micronutrient fertilizer management especially zinc (Zn) through the soil and foliar application is crucial agronomic approach for improving agronomic biofortification of staple grains crops. The intervention of plant growth-promoting bacteria (PGPBs) could be one of the sustainable and safe strategies to improve nutrient acquisition and uptake in edible tissues of wheat-maize and common beans to combat Zn malnutrition and hidden hunger in human beings. In this context, this research was developed to understand the interactive effect of inoculation/ co-inoculation with PGPBs and Zn fertilization via soil and foliar to enhance growth performance, yield, and nutrition of wheat-maize and common bean crops for better biofortification of grains under field conditions of tropical savannah. A total of six experiments were performed in a randomized complete block design in Rhodic Haplustox soil under no-tillage system. Experiment 1 with common bean was conducted in 7 × 2, co-inoculation with PGPBs (no inoculation, Rhizobium tropici, R. tropici + Azospirillum brasilense, R. tropici + Bacillus subtilis, R. tropici + Pseudomonas fluorescens, R. tropici + A. brasilense + B. subtilis, and R. tropici + A. brasilense + P. fluorescens) in association with soil Zn application (without and 8 kg ha−1, applied from zinc sulphate) during 2019 and 2020 (May-August). Experiment 2 with common beans was conducted in 7 × 3 factorial scheme, co-inoculation with PGPBs (no inoculation, Rhizobium tropici, R. tropici + Azospirillum brasilense, R. tropici + Bacillus subtilis, R. tropici + Pseudomonas fluorescens, R. tropici + A. brasilense + B. subtilis, and R. tropici + A. brasilense + P. fluorescens) in association foliar nano-Zn doses (0, 1.5 and 3.0 kg ha-1, applied from zinc oxide) during 2019 and 2020 (May-August). Exeriment 3 with wheat was conducted in 4 × 2 factorial scheme, inoculations with PGPBs (no inoculation - control, A. brasilense, B. subtilis and P. fluorescence) in association with soil Zn application (0 and 8 kg ha−1) during 2019 and 2020 (May-September). Experiment 4 with wheat was conducted in 4 × 5 factorial scheme, inoculations with PGPBs (no inoculation - control, A. brasilense, B. subtilis and P. fluorescence) in association with five foliar nano-Zn doses (0, 0.75, 1.5, 3.0 and 6.0 kg ha−1) during 2019 and 2020 (May-September). Experiment 5 with maize was performed in 4 × 2 factorial scheme, inoculations with PGPBs (no inoculation - control, A. brasilense, B. subtilis and P. fluorescence) in association with soil Zn application (0 and 8 kg ha−1) during 2019–2020 and 2020–2021 (November-March). Experiment 6 with maize was also performed 4 × 2 factorial scheme, inoculations with PGPBs (no inoculation - control, A. brasilense, B. subtilis and P. fluorescence) in association with two foliar nano-Zn doses (0 and 3 kg ha−1) during 2019–2020 and 2020–2021 (November-March). Co-inoculation with R. tropici + B. subtilis and R. tropici + P. fluorescens along with soil and foliar Zn application improve plant growth, grain yield and nitrogen (N), phosphorous (P) and Zn concentrations in shoot and grains of common bean. Zinc use efficiency, applied Zn recovery, and utilization were also increased with co-inoculation of R. tropici + B. subtilis along with soil Zn application and foliar nano-Zn application at a dose of 1.5 kg ha−1 whereas agro-physiological efficiency was increased with triple co-inoculation of R. tropici + A. brasilense + P. fluorescens. Inoculation with B. subtilis improved maize grain yield (14-17%), while inoculation with P. fluorescens improve Zn accumulation in shoot (33-51%) and grains (37-50.7%) of maize under residual Zn and nano-Zn foliar fertilization in wheat-maize succession. In addition, biochemical attributes (chlorophyll a, b and total, carotenoids, total soluble sugar and amino acids) and Zn use efficiency were also increased with inoculation B. subtilis and P. fluorescens in combination with soil and nano-Zn foliar application. Inoculation with B. subtilis and P. fluorescens along with soil Zn and nano-Zn foliar application improved Zn concentration of shoot (18-31%) and grains (16-34%), N concentration of shoot (10-24%) and grains (16-20%), P concentration of shoot (26-32%) and grains (18-26%), and grain yield (4-20.6%) of wheat in tropical savannah. Also, inoculation of P. fluorescence with soil and foliar Zn application improved zinc use efficiency and utilization efficiency that increased Zn partitioning to edible grains for higher estimated Zn intake in with daily wheat consumption. Therefore, inoculation of B. subtilis and P. fluorescens with soil and foliar nano-Zn application is considered one of the most effective, sustainable and environmentally safe strategy for improving biochemical, nutritional and productivity attributes of common beans, maize and wheat cropping system. Hence, it is recommended that seed inoculation with B. subtilis and P. fluorescens along with Zn fertilization via soil or foliar nano-Zn at a dose 3 kg ha-1 could be an effective mechanism to improve plant nutrients acquisition and use efficiencies particularly Zn, leading to sustainable production and biofortification of common beans, wheat and maize under tropical savannah regions of Brazil.

O sistema de cultivo intensivo para buscar alta produção de grãos e alimentar a população global em rápido crescimento tem prejudicado a sustentabilidade agrícola e a segurança alimentar devido ao uso desequilibrado de fertilizantes minerais. Há uma necessidade urgente de entender o baixo teor de micronutrientes no solo e seu impacto na nutrição e produtividade das culturas. O manejo de fertilizantes com micronutrientes, especialmente zinco (Zn) aplicado no solo e via foliar, é uma abordagem agronômica crucial para melhorar a biofortificação agronômica de culturas graníferas. A aplicação de bactérias promotoras de crescimento vegetal (PGPBs) pode ser uma das estratégias sustentáveis e seguras para melhorar a aquisição e absorção de nutrientes em tecidos comestíveis de trigo-milho e feijão comum para combater a desnutrição de Zn e a fome oculta em seres humanos. Nesse contexto, esta pesquisa foi desenvolvida para entender o efeito interativo da inoculação/coinoculação com bactérias promotoras de crescimento de planats (BPCP) e adubação com Zn via solo e foliar para melhorar o crescimento, produtividade e nutrição das culturas de trigo-milho e feijão, além de averiguar a biofortificação de grãos em condições de campo de Cerrado tropical. Para isso, realizou-se seis experimentos, todos em delineamento de blocos casualizados em Latossolo vermelho de textura argilosa sob sistema plantio direto. O experimento 1 com feijão comum foi conduzido em esquema fatorial 7 × 2, sendo co-inoculação com PGPBs (sem inoculação, Rhizobium tropici, R. tropici + Azospirillum brasilense, R. tropici + Bacillus subtilis, R. tropici + Pseudomonas fluorescens, R. tropici + A. brasilense + B. subtilis e R. tropici + A. brasilense + P. fluorescens) e aplicação de Zn no solo (sem e 8 kg ha−1, como sulfato de zinco) em 2019 e 2020 (maio-agosto). O experimento 2 com feijão comum foi conduzido em esquema fatorial 7 × 3, sendo co-inoculação com PGPBs (sem inoculação, R. tropici, R. tropici + . brasilense, R. tropici + B. subtilis, R. tropici + Pseudomonas fluorescens, R. tropici + A. brasilense + B. subtilis, e R. tropici + A. brasilense + P. fluorescens) em associação a doses foliares de nano-Zn (0, 1,5 e 3,0 kg ha-1 de Zn, como óxido de zinco) em 2019 e 2020 (maio-agosto). O experimento 3 com trigo foi conduzido em esquema fatorial 4 × 2, sendo inoculações com PGPBs (sem inoculação - controle, A. brasilense, B. subtilis e P. fluorescens) em associação com aplicação de Zn no solo (0 e 8 kg ha-1) em 2019 e 2020 (maio a setembro). O experimento 4 foi conduzido com trigo em esquema fatorial 4 × 5, sendo inoculações com PGPBs (sem inoculação - controle, A. brasilense, B. subtilis e P. fluorescens) em associação com cinco doses foliares de nano-Zn (0, 0,75, 1,5, 3,0 e 6,0 kg ha-1 de Zn) em 2019 e 2020 (maio-setembro). O experimento 5 com milho foi realizado em esquema fatorial 4 × 2, sendo inoculações com PGPBs (sem inoculação - controle, A. brasilense, B. subtilis e P. fluorescens) em associação com aplicação de Zn no solo (0 e 8 kg ha-1) em 2019–2020 e 2020–2021 (novembro-março). Também foi realizado experimento 6 com milho em esquema fatorial 4 × 2, sendo inoculações com PGPBs (sem inoculação - controle, A. brasilense, B. subtilis e P. fluorescens) em associação com duas doses foliares de nano-Zn (0 e 3 kg ha−1 de Zn) em 2019–2020 e 2020–2021 (novembro-março). A coinoculação com R. tropici + B. subtilis e R. tropici + P. fluorescens juntamente com a aplicação de Zn no solo e foliar melhoram o crescimento da planta, a produtividade de grãos e as concentrações de nitrogênio (N), fósforo (P) e Zn na parte aérea e nos grãos de feijão comum. As eficiências de uso do zinco, de recuperação e de utilização do Zn aplicado também foram aumentadas com a coinoculação de R. tropici + B. subtilis juntamente com a aplicação de Zn no solo e aplicação foliar de nano-Zn na dose de 1,5 kg ha-1, enquanto a eficiência agrofisiológica aumentou com a coinoculação tripla de R. tropici + A. brasilense + P. fluorescens. A inoculação com B. subtilis aumentou a produtividade de grãos de milho (14-17%), enquanto a inoculação com P. fluorescens incrementou o acúmulo de Zn na parte aérea (33-51%) e grãos (37-50,7%) de milho sob Zn residual no solo e nano-Zn adubação foliar na sucessão trigo-milho. Além disso, atributos bioquímicos (clorofila a, b e total, carotenóides, açúcar solúvel total e aminoácidos) e eficiência de uso de Zn também foram aumentados com a inoculação de B. subtilis e P. fluorescens em combinação com solo e aplicação foliar de nano-Zn. A inoculação com B. subtilis e P. fluorescens juntamente com a aplicação foliar de nano-Zn e Zn no solo melhorou a concentração de Zn na parte aérea (18-31%) e grãos (16-34%), a concentração de N na parte aérea (10-24%) e grãos (16-20%), concentração de P na parte aérea (26-32%) e grãos (18-26%) e produtividade de grãos (4-20,6%) de trigo em cerrado tropical. Além disso, a inoculação de P. fluorescens com Zn aplicado no solo ou aplicação foliar de Zn melhorou a eficiência de uso de zinco e aumentou a partição de Zn em grãos comestíveis para maior ingestão estimada de Zn com consumo diário de trigo. Portanto, a inoculação de B. subtilis e P. fluorescens com aplicação de Zn no solo ou foliar de nano-Zn são consideradas estratégias mais eficazes, sustentáveis e ambientalmente seguras para melhorar os atributos bioquímicos, nutricionais e de produtividade de feijão, milho e trigo em sistemas agrícolas. Portanto, recomenda-se que a inoculação de sementes com B. subtilis e P. fluorescens juntamente com a fertilização de Zn via solo ou nano-Zn foliar na dose de 3 kg ha-1, por ser um mecanismo eficaz para melhorar a eficiência de aquisição e uso de nutrientes pelas plantas, particularmente Zn, propiciando uma produção mais sustentável e biofortificação de feijão comum, trigo e milho em regiões de cerrado tropical do Brasil.
Biofortificação agronômica de culturas graníferas com zinco em associação com bactérias promotoras de crescimento de plantas
Keywords: Phaseolus vulgaris L.; Triticum aestivum L.; Zea mays L.; Zinc fertilization; Zinc uptake; Zinc use efficiency; Zinc partitioning; Productivity; Zinc nutrition; Inoculation; Fertilização com zinco; Absorção de zinco; Eficiência de uso do zinco; Partição de zinco; Produtividade; Nutrição de zinco; Inoculação